2007
DOI: 10.1021/ol7020675
|View full text |Cite
|
Sign up to set email alerts
|

Latrunculin with a Highly Oxidized Thiazolidinone Ring:  Structure Assignment and Actin Docking

Abstract: A new latrunculin, oxalatrunculin B (3), was isolated from Red Sea sponge Negombata corticata. Extensive spectroscopic analysis revealed an unprecedented heterocycle in which the rare thiazolidinone ring found in latrunculins was oxidized with three additional oxygens. An actin polymerization inhibition assay agreed with MM-PBSA free energy calculations that 3 binds more weakly than latrunculin B to actin. Significant antifungal and anticancer activity of 3 was found, suggesting an alternate target in addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 12 publications
2
23
0
1
Order By: Relevance
“…The compound structure is a 14- or 16-membered macrolide base attached to a 2-thiazolidinone moiety [52]. Latrunculin A was found to inhibit the invasion of the tumorigenic AdoMetDC transformants of murine fibroblasts [53], the human breast cancer G3S1 cell line [54] and HeLa-O3 cells [55].…”
Section: Candidate Migrastatic Drugsmentioning
confidence: 99%
“…The compound structure is a 14- or 16-membered macrolide base attached to a 2-thiazolidinone moiety [52]. Latrunculin A was found to inhibit the invasion of the tumorigenic AdoMetDC transformants of murine fibroblasts [53], the human breast cancer G3S1 cell line [54] and HeLa-O3 cells [55].…”
Section: Candidate Migrastatic Drugsmentioning
confidence: 99%
“…Cytotoxicity of oxalatrunculin B against several cancer cell lines suggested that compound 32 displayed nonspecific cytotoxicity against solid tumor cells and hematopoietic cancerous cells, possessing MIC value of 16.3 μM against hepatocellular carcinoma. The weak binding to actin and the stronger cytotoxic activity suggest that may exist a secondary target responsible for the different activities of 32 [60]. Austin et al patented a series of N -hydroxy derivatives as industrial biocides.…”
Section: N-hydroxy-substituted Five-membered Heterocyclesmentioning
confidence: 99%
“…Thiazolidinone moiety is an important structure element in medicinal chemistry [2][3][4][5][6] and substituted thiazolidinones show a broad spectrum of biological activities [7][8][9][10][11] [16].Therefore, facile preparation of various 5-arylidene thiazolidinones is highly desirable. In continuation of our ongoing interests in the development of benign methods targeted at the synthesis of biologically important heterocycles [17][18][19], we used base supported ionic liquid-like phase (SILLP) [20] as an efficientand recyclablesolid phasecatalystinthe synthesis of thetitle compound.…”
Section: Discussionmentioning
confidence: 99%
“…Thiazolidinone moiety is an important structure element in medicinal chemistry [2][3][4][5][6] and substituted thiazolidinones show a broad spectrum of biological activities [7][8][9][10][11]. In particular, 5-arylidene-4-thiazolidinones have been synthesized and employed as new agents with SHP-2 inhibitory action [12],aspotential antifungal and antibacterial drugs [13],asPTP1Band LMW-PTP inhibitors [14],a nti-inflammatory agent [15] and antimicrobial drugs [16].Therefore, facile preparation of various 5-arylidene thiazolidinones is highly desirable.…”
Section: Discussionmentioning
confidence: 99%